Acoustic Properties of Nanofibers. (November 2014) - Iannace, Gino
In recent years nanofibers have been used in the field of applied acoustics to improve the acoustic characteristics of traditional materials without increasing their weight and size. In this paper acoustic measurements are reported of the absorption coefficient of porous materials coated with a layer of nanofibers carried out with the impedance tube ("Kundt" tube) in the frequency range of 200 Hz – 6.3 kHz. The layers of nanofibers are obtained by NY6 (nylon) based on needle - free electro-spinning process available at "Next Technology Tecnotessile r.l." (Prato, Italy). The layer of nanofibers is glued on different types of porous materials with different thicknesses. The values of the absorption coefficient measured at normal incidence, were compared with the values carried out on porous materials with and without the layer of nanofibers.